Estimate of JAK 2 V617F Mutation and Activity of Catalase Enzyme in Myeloproliferative Neoplasm - Abdullah, Heba Rushdi; Saifullah, Perry Habib; Shebib, Ziad Ahmed; Abdullah, Ahmed Rushdi (Al-Nahrain Journal of Science, 2016)
Background: Myeloproliferative neoplasms (MPNs) are a range of clonal hematological diseases with overlapping features, a specific mutation in the JAK2 gene, which encodes a tyrosine Kinase has been shown to be associated with the myeloproliferative phenotypes (PV, ET and PMF). Aim: Estimate the proportion of JAK2 V617F mutant gene and estimate the significance of antioxidant enzyme (Catalase) is mainly associated with increased oxidative stress this is resulting increase of the free oxygen radicals and relate it with suspected myeloproliferative neoplasms (MPNs) in Iraqi patients. Materials and Methods: Total of (51) patients with suspected myeloproliferative neoplasms (MPNs) and 20 healthy individuals were analyzed for the JAK2 V617F mutation. After DNA extraction, detection of the mutation was done using (ARMS) PCR amplification, activity of Catalase was measured spectrophotometrically. Results: Of 51 patients, the JAK2 V617F mutation (V617F) was detected in 33 out of 42, with PV (81%), and four of patients with ET and PMF (40% and 50%, respectively). The prevalence of this mutation is more associated with male than female about (62%). Catalase activity was found highly significant (P< 0.01) among suspected MPN patients when compared with control group. Conclusion: JAK2 V617F mutation screening can be incorporated in the initial estimate of patients suspected of having MPNs. Catalase enzyme used a biomarker of enzymatic alteration in MPN Iraqi patients.